2019
DOI: 10.1002/hed.25615
|View full text |Cite
|
Sign up to set email alerts
|

African head and neck fellowships: A model for a sustainable impact on head and neck cancer care in developing countries

Abstract: Background There is an extreme shortage of head and neck surgeons in Africa. Fourteen head and neck surgeons have completed fellowships in Cape Town and Cameroon. This study determines whether such Africa‐based fellowships are a good model for developing countries by making a sustainable impact on head and neck cancer care. Methods An observational study was conducted by emailing questionnaires to past fellows. Results All fellows had returned to teaching hospitals in their counties. Seven established new mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…The authors concluded that high volume, specialized head and neck surgical training was possible in Africa; and that training was appropriate in terms of pathology and types of surgery. They also concluded that the fellowships had made a sustainable contribution to head and neck practice in Sub‐Saharan Africa by populating it with surgeons and teachers of head and neck surgery, by them establishing centers of excellence, by building clinical capacity, and by instituting resource appropriate management 7 . The African Head and Neck Society (AfHNS) is currently formulating an AfHNS ‐endorsed fellowship programme to increase training opportunities at more training centers in Africa.…”
Section: African Head and Neck Surgery Fellowship Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that high volume, specialized head and neck surgical training was possible in Africa; and that training was appropriate in terms of pathology and types of surgery. They also concluded that the fellowships had made a sustainable contribution to head and neck practice in Sub‐Saharan Africa by populating it with surgeons and teachers of head and neck surgery, by them establishing centers of excellence, by building clinical capacity, and by instituting resource appropriate management 7 . The African Head and Neck Society (AfHNS) is currently formulating an AfHNS ‐endorsed fellowship programme to increase training opportunities at more training centers in Africa.…”
Section: African Head and Neck Surgery Fellowship Trainingmentioning
confidence: 99%
“…Only about 5% of patients in Africa and 3% in South Asia have timely access to safe, affordable surgery (Figure 1). 6 Sub‐Saharan Africa has only 18 fellowship‐trained head and neck surgeons for its >1 billion people 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,6 Given the inadequate global chemotherapy and radiotherapy capacity, 7,8 surgical care is a particularly important intervention as it is often the primary mode of diagnosis and treatment for early stage HNC. 3,5,9 However, many low- and middle-income country health systems have limited surgical capacity in part due to surgical workforce shortages and geographic maldistribution of providers, reducing the likelihood that patients receive timely surgical care. 10 In 2015, the Lancet Commission on Global Surgery (LCoGS) convened a group of experts to provide estimates on the global burden of surgical disease and to identify avenues to advance surgical system strengthening.…”
mentioning
confidence: 99%
“…That might include the use of the WhatsApp platform by community health workers in Uganda to share cases of ear disease in their local village, 2 or the same platform used by geographically dispersed nonspecialist surgeons in the Pacific islands to discuss management of ENT pathology. The Internet can also be exploited to assist diagnosis: For instance, half of African head and neck surgeons reported that poorly developed histopathology services were an obstacle to providing care, 3 but now that histology slides can be transmitted online for diagnosis by experts in a remote location, 4 such barriers could be overcome. This has been taken further, with an entire multi-disciplinary team (MDT) available online.…”
Section: Virtual C a S E Discussionmentioning
confidence: 99%